Exploratory study of spiral NC tool path generation on triangular mesh based on local subdivision. Issue 5 (March 2016) - Zhang, Zixian; Feng, Yixiong; Ren, Bingyin; Hagiwara, Ichiro
Abstract As a representation of free-form surface, triangle mesh model (commonly with the stereo lithography format) has gained wide application in CAD and CAM recently because of its simple geometric computation, superior robustness, and high efficiency in tool path generation. However, conventional tool-path generation methods for NURBS surface are incapable of direct application to mesh models. Development of a tool-path generation method based on mesh model with high machining precision is becoming a key problem for NC machining. In this paper, a spiral tool-path generation method in finish-cut process is developed based on the offset-surface method (also called cutter location method). A novel local subdivision method is proposed firstly to guarantee edges of the offset-mesh within the required tool-path interval, and then gouge-free tool-path is generated by organizing path through vertex of the offset-mesh. Therefore, all the path intervals are under precise control by the local subdivision, allowing the mesh surface with both steeper and flatter areas to be machined with high-precision. Besides, tool-path naturally runs along the boundary of the triangle mesh model, ensuring continuous cut for reducing the fluctuation of cutting load. At last, tool-paths with multiple connective areas are generated for several complex mesh surfaces to clarify efficiency and robust of proposed method.